MALACHI’S CONTROVERSIAL CONCLUSION: (Acta Theologica)
This contribution briefly outlines some of the prominent problems encountered in Malachi 3:22-24 (Eng. 4:4-6). The question posed can be formulated as an investigation of the most important problems that confront research on this final part of the book of Malachi and, secondly, what possible prospects are there to solve (at least some of) the problems? This contribution argues that Malachi 3:22-24 (Eng. 4:4-6) should be viewed as two (Mal. 3:22 and 3:23-24, respectively) later additions to the book. It is also argued that the reading of the Septuagint, where verse 22 is placed as the last verse of the book, should be accepted as the better reading. Verses 23-24 were initially added to serve as an update to the previous unit (Mal. 3:13-21).